The Radiological Assessment to determine whether the use of assistive devices improve Syndesmotic screw placement during surgical fixation of ankle fractures - Kriel, Renier (Stellenbosch : Stellenbosch University, 2022)
Thesis (MMed) -- Stellenbosch University, 2022.